Fostering Creativity Among Pandanrejo Village Residents via Ecoprinting to Improve the Added Value of Tote Bags with Tannin Leaves - Dwi Danty Aisyah; Muhammad Aufan Akmal; Aisyah Trining Tias Tias; Calista Salsabilla Sudrajat Sudrajat; Ilham Alif Sadili Sadili; Tuhfatul Mardiyah; Wahyu Hariyanto (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The community service activity conducted by the Student Work Lecture Group (KKM) of the State Islamic University of Maulana Malik Ibrahim Malang in Pandanrejo Village aimed to introduce eco print techniques on calico tote bags as a means of fostering residents' creativity and economic empowerment. Using the Participatory Action Research (PAR) approach, the program involved socialization, mentoring, and hands-on training with the pounding method, in collaboration with 35 mothers from the PKK cadre group. Participants utilized tannin-rich local leaves, including guava, cassava, teak, and betel leaves, to create distinctive natural colors and patterns. The training enhanced participants' creativity, confidence, and ability to experiment with varied motifs, while raising awareness of the added economic value of eco printed tote bags compared to plain ones. This environmentally friendly initiative expanded knowledge of natural resource utilization, motivated the transformation of local materials into higher-value products, and laid a foundation for sustainable creative industry development and long-term community welfare.